2010
DOI: 10.1590/s1984-46702010000600009
|View full text |Cite
|
Sign up to set email alerts
|

Correction of the weight and length for juveniles Atherinella brasiliensis (Actinopterygii: Atherinopsidae) after fixation in formalin and preservation in ethanol

Abstract: The present study compared losses of weight and length in specimens of Atherinella brasiliensis (Quoy & Gaimard, 1825) after fixation in formalin 10% during ten days, and posterior preservation in ethanol 70% for 45 days, in two solvents: freshwater and marine water. Additionally, correction factors were proposed to calculate the correction for weight and length from preserved specimens. The specimens were weighted and measured after collection (fresh), and with 10, 20, 27, 34, 41 and 55 days of fixation plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…By presenting multiple staging methods and descriptions of development, additional tools are provided to researchers that complement morphological stages. A common practice in embryo studies involves preserving samples in fixatives such as ethanol or formaldehyde; which have been reported to cause embryo shrinkage (Melo et al ., ; Vergara‐Solana et al ., ). This study presents the effects of two common fixatives, ethanol and formalin, on embryo morphometrics to assist researchers in both the staging and use of embryos for morphological measurements following fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By presenting multiple staging methods and descriptions of development, additional tools are provided to researchers that complement morphological stages. A common practice in embryo studies involves preserving samples in fixatives such as ethanol or formaldehyde; which have been reported to cause embryo shrinkage (Melo et al ., ; Vergara‐Solana et al ., ). This study presents the effects of two common fixatives, ethanol and formalin, on embryo morphometrics to assist researchers in both the staging and use of embryos for morphological measurements following fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the combined effects of formalin and ethanol on species of fishes post hatch. Other studies have reported similar embryo shrinkage trends (Melo et al ., ; Vergara‐Solana et al ., ). The change in L T from fixed (10% formalin followed by 70% ethanol) to unfixed individuals has been found to range from 5·7% in golden mojarra Deckertichthys aureolus (Jordan & Gilbert 1882) (Vergara‐Solana et al ., ) to 11·77% in juvenile Brazilian silverside Atherinella brasiliensis (Quoy & Gaimard 1825) (Melo et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Captured specimens were anaesthetized with MS 222 and preserved in 10% formalin, then transferred to the Department of Fisheries and Aquaculture (Gaziosmanpasa University, Turkey). The largest losses in weight and length due to formalin are known to occur during the first three weeks, and then begin to stabilize after about six weeks (Melo et al., ). All specimens from each location were affected by formalin in a same manner.…”
Section: Methodsmentioning
confidence: 99%
“…To do this, we re-photographed 13 specimens retained as vouchers after they had been preserved in ethanol after four months and again after four years. Since body length has been shown to stabilize after less than two months of preservation [23], [24], [25], we considered four months to be adequate time in preservative to observe an effect and four years enough time to test if the shrinkage had stabilized. In line with these previous studies, we expected some characters, such as SVL, to shrink significantly in preservative and others, such as features of the bony cranial crests, to show little, if any, change [22].…”
Section: Methodsmentioning
confidence: 99%